Assessment of interleukin-6 level and lung inflammatory cells after high-intensity interval training and stay in hypoxic conditions - M yadegari; S riahy; Sh mirdar; Gh hamidian; P mosadegh (فصلنامه ابن سینا)
Background: It seems that the effect of training on improving physical performance is not always associated with beneficial effects on internal organs. So far, the effects of high-intensity interval training and subsequent exposure to hypoxia have not been investigated on lung parenchyma. The purpose of this study was to investigate the effects of chronic hypoxia followed by high-intensity interval training on amount of lung inflammation.